Effects of H2O and SO2 on Selective Catalytic Reduction of NOx by NH3 - Bai, Shuzhan; Tao, Jianzhong; Sun, Qiang; Tong, Dehui; Li, Guoxiang (Asian Journal of Chemistry, 2012)
Experiments have been investigated to study the effects of H2O and SO2 contents on NOx reduction efficiency using ammonia (NH3) as the reducing agent over the nanometer-class V-W/Ti catalyst under variable temperatures on a steady-flow reactor. The results show that the activity of selective catalytic reduction (SCR) is inhibited by H2O content at low temperature, but higher NO conversion efficiency should be achieved at high temperature due to the reaction of NH3 oxidized by O2 to NOx would be inhibited by H2O content. The selective catalytic reduction activity will be promoted by SO2 content in the range of 150-500 ºC, NO conversion efficiency can be improved to 98 % from 94 % by adding SO2 content. The activity of selective catalytic reduction will be promoted at 150-240 ºC and 350-500 ºC when H2O and SO2 exist at the same time, but ammonium sulfates and other sulfates will be generated at low temperature. Additionally, following the ESC test, the positive influence to the NOx conversion has been proved in the presence of H2O and SO2, but it has considerably negative effect to PM emission for the diesel engine.